Pulsed electric field ablation process-the effect of bifurcation stents on electric field and heat distribution - Zhen wang; Jingyang Sun; Ming Liang; Jie Zhang; Yulai Yan; Fengqi Xuan; Lisheng Xu; Yaling Han (Scientific Reports)
Abstract Pulsed field ablation (PFA) is a novel non-thermal technique for arrhythmia treatment, capable of targeting the epicardium. However, the effects of coronary bifurcation lesions (BL) and bifurcation stents (BS) on ablation efficacy have not been evaluated. A three-dimensional computer simulation model was developed to assess the effect of the ablation region. The ablation catheter was set to be located directly above the BS model by performing a true size reduction of the ablation device. The ablation region was evaluated using an electric field strength contour of 1000 V/cm. The influence of coronary BL and BS on PFA ablation efficacy was assessed using ablation effect maps from different models. BS did not induce electric field coupling, and the distortion of the electric field in the ablation region remained unchanged, with cold and hot spots located similarly. The presence of coronary branches reduced the ablation area width, with a maximum difference of 2.82 mm. The angle between the ablation catheter and the main coronary artery branch had a smaller effect on the ablation zone width, with a maximum difference of 1.24 mm. The presence of BS will have a positive effect on the temperature increase in the ablation region (3.59 °C temperature increase in the presence of BS). The results indicate that BL and BS influence the electric field distribution in the ablation region. However, this distortion is confined to the ablation area, with no coupling between the main coronary artery and its branches to exacerbate the electric field distortion. The presence of BS exacerbates the temperature rise at the ablation site, but this increase does not cause thermal damage to the region.